Characterization of implicit and explicit mind-reading in children with autism based on eye movements - Lu, Haidan; Niu, Juanli; Wang, Jiaxin; Liu, Min; Xu, Mingyu (Frontiers in Psychiatry, 2024)
Objective This study aimed to investigate differences in mind-reading abilities between children with autism and typically developing children across various tasks. Methods Sixteen children with autism (aged 5-8 years) were compared to 16 typically developing children matched in language ability. The unexpected location task and unexpected content task were used to assess implicit and explicit mind-reading abilities using an eye tracker and illustrated storybooks. Results For implicit mind, using differential looking scores shows a no significant difference between the scores of children with autism and typically developing children in the implicit tasks (P=0.399). However, the pupil size show some significant difference between two groups. Second, for the explicit, a significant difference between the scores of children with autism and typically developing children in the explicit tasks (P=0.006). Additionally, only a significant correlation between implicit and explicit mind-reading abilities in children with autism in the unexpected location task was found. Conclusion The mechanism of implicit mind-reading still not very clear. Pupil-Linked arousal response can be consider as a further tool. Further research on implicit and explicit mind-reading abilities is warranted.